Monopolies and restrictive trade practices act, 1969 ( Act no. 54 of 1969) - India. Ministry of Law and Justice (New Delhi, 1997)
An Act to provide that the operation of the economic system does not wwel in the concentration of economic power to the common detriment. for the control of monopolies, for the prohibition of monopolistic and restric the trade practices and for matters connected therewith or incidental thereto.
Keywords: Trade act-India-1969